2020
DOI: 10.1021/acs.energyfuels.0c00492
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Review of the Impact of 2,5-Dimethylfuran and 2-Methylfuran on Soot Emissions: Experiments in Diesel Engines and at Laboratory-Scale

Abstract: 2,5-Dimethylfuran (2,5-DMF) and 2-methylfuran (2-MF) are furan derivatives that are shown to be able to reduce soot emissions from diesel engines. However, their capacity to form soot is high due to their cyclic structures. Therefore, the question arises that if the tendency to form soot of these oxygenated compounds is high, how do they have the ability to reduce soot emissions when added to diesel fuel. The operating conditions, as well as their physicochemical and combustion characteristics, can contribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 212 publications
0
12
0
Order By: Relevance
“…Most notably, DMF is considered as a potential furan derivative to improve combustion characteristics and reduce negative emissions from SI engines (Balasubramanian et al, 2021) (Engel et al, 2021) compared to ethanol and gasoline (Ya et al, 2020) (Tran et al, 2021). In addition, the advantages of stratified flame characteristics may open up potential applications of furan-based fuels for efficient applications in CI engines (Sandro and Viet, 2020) (Alexandrino, 2020) (Ölçer and Nižetić, 2021). In short, a bright prospect to wake up the DMF giant is entirely possible in the coming decades.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…Most notably, DMF is considered as a potential furan derivative to improve combustion characteristics and reduce negative emissions from SI engines (Balasubramanian et al, 2021) (Engel et al, 2021) compared to ethanol and gasoline (Ya et al, 2020) (Tran et al, 2021). In addition, the advantages of stratified flame characteristics may open up potential applications of furan-based fuels for efficient applications in CI engines (Sandro and Viet, 2020) (Alexandrino, 2020) (Ölçer and Nižetić, 2021). In short, a bright prospect to wake up the DMF giant is entirely possible in the coming decades.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…MF can be produced from non-edible biomass [4][5][6] and the potential of MF as surrogate fuel on engine has been proved [7,8]. As shown in Table 1 [9][10][11], the boiling point of MF is similar with gasoline, and its high octane number makes it suitable as a substitute for gasoline. In addition, MF has several advantages over smaller alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 Properties of diesel, biodiesel, ethanol, gasoline and MF [9][10][11] The applicability of MF fuel as gasoline surrogate fuel or diesel additives in internal combustion engines has been experimentally evaluated in many studies. Wang et al [7] investigated the performance of a direct-injection spark-ignition (DISI) engine fueled with MF, ethanol, gasoline and 2,5-dimethylfuran (DMF).…”
Section: Introductionmentioning
confidence: 99%
“…However, under 3.5 bar IMEP, MF emitted 82%, 281% and 40% more NOx than gasoline, ethanol and 2,5-dimethylfuran (DMF), respectively. Katiuska [7] described the characteristics of soot formation during combustion of diesel blended with MF or DMF and found that the reduction of soot emission from the diesel engine was due to different factors when using a diesel / furan derivative mixture, such as operating conditions, and combustion characteristics and physiochemical properties of the fuel. Xiao et al [8] showed that when the pre-injection ratio was 20%, HC and CO emissions were greatly reduced, but NOx emissions increased after MF was added into the pre-injection fuel.…”
Section: Introductionmentioning
confidence: 99%